Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine the solution to the given system of equations, we need to find the point at which the two lines intersect. Here are the equations:
1. [tex]\( y = 3x + 9 \)[/tex]
2. [tex]\( 6x + 2y = 6 \)[/tex]
### Step-by-Step Solution
#### Step 1: Convert the Second Equation to Slope-Intercept Form
The second equation is [tex]\( 6x + 2y = 6 \)[/tex]. To express this equation in the slope-intercept form [tex]\( y = mx + b \)[/tex], follow these steps:
1. Subtract [tex]\( 6x \)[/tex] from both sides:
[tex]\[ 2y = 6 - 6x \][/tex]
2. Divide every term by 2:
[tex]\[ y = -3x + 3 \][/tex]
Now, we have the two equations in slope-intercept form:
- [tex]\( y = 3x + 9 \)[/tex]
- [tex]\( y = -3x + 3 \)[/tex]
#### Step 2: Find the Intersection Point
To find the point of intersection, set the right-hand sides of the equations equal to each other:
[tex]\[ 3x + 9 = -3x + 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
1. Add [tex]\( 3x \)[/tex] to both sides:
[tex]\[ 6x + 9 = 3 \][/tex]
2. Subtract 9 from both sides:
[tex]\[ 6x = -6 \][/tex]
3. Divide by 6:
[tex]\[ x = -1 \][/tex]
With [tex]\( x = -1 \)[/tex], substitute this value into one of the original equations to find [tex]\( y \)[/tex]. Using [tex]\( y = 3x + 9 \)[/tex]:
[tex]\[ y = 3(-1) + 9 = -3 + 9 = 6 \][/tex]
Therefore, the solution to the system is [tex]\( (-1, 6) \)[/tex].
### Conclusion
The system of equations has one unique solution: [tex]\( (-1, 6) \)[/tex].
The graphical representations of these equations will intersect at this point. Consequently, the correct answer is:
There is one unique solution [tex]\((-1, 6)\)[/tex].
1. [tex]\( y = 3x + 9 \)[/tex]
2. [tex]\( 6x + 2y = 6 \)[/tex]
### Step-by-Step Solution
#### Step 1: Convert the Second Equation to Slope-Intercept Form
The second equation is [tex]\( 6x + 2y = 6 \)[/tex]. To express this equation in the slope-intercept form [tex]\( y = mx + b \)[/tex], follow these steps:
1. Subtract [tex]\( 6x \)[/tex] from both sides:
[tex]\[ 2y = 6 - 6x \][/tex]
2. Divide every term by 2:
[tex]\[ y = -3x + 3 \][/tex]
Now, we have the two equations in slope-intercept form:
- [tex]\( y = 3x + 9 \)[/tex]
- [tex]\( y = -3x + 3 \)[/tex]
#### Step 2: Find the Intersection Point
To find the point of intersection, set the right-hand sides of the equations equal to each other:
[tex]\[ 3x + 9 = -3x + 3 \][/tex]
Solve for [tex]\( x \)[/tex]:
1. Add [tex]\( 3x \)[/tex] to both sides:
[tex]\[ 6x + 9 = 3 \][/tex]
2. Subtract 9 from both sides:
[tex]\[ 6x = -6 \][/tex]
3. Divide by 6:
[tex]\[ x = -1 \][/tex]
With [tex]\( x = -1 \)[/tex], substitute this value into one of the original equations to find [tex]\( y \)[/tex]. Using [tex]\( y = 3x + 9 \)[/tex]:
[tex]\[ y = 3(-1) + 9 = -3 + 9 = 6 \][/tex]
Therefore, the solution to the system is [tex]\( (-1, 6) \)[/tex].
### Conclusion
The system of equations has one unique solution: [tex]\( (-1, 6) \)[/tex].
The graphical representations of these equations will intersect at this point. Consequently, the correct answer is:
There is one unique solution [tex]\((-1, 6)\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.